A battery separator and a preparation method thereof and a battery
By using composite materials of nanocellulose and metal-organic frameworks in lithium-ion battery separators, combined with a second coating containing cations and dopamine, the problems of insufficient melting, shrinking and mechanical strength of the separators at high temperatures are solved, and higher safety and kinetic performance are achieved.
Patent Information
- Application Number
- CN202510073303.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing lithium-ion battery separators are prone to melt and shrink at high temperatures, and are prone to piercing by burrs and lithium dendrites inadequate strength. Poor wetting properties affect battery performance, and the thermal insulation performance is insufficient to effectively prevent thermal runaway.
The composite material in the first coating, including nanocellulose and metal organic framework, is used to cooperate to improve the high temperature resistance characteristics, pore structure and specific surface area of the membrane, enhance mechanical strength and density, and cation-containing ionic liquid and/or dopamine-containing compounds are added to the second coating to enhance electrochemical performance.
It significantly reduces the probability of thermal runaway, improves the liquid absorption rate and the migration rate of lithium ions, and enhances the safety, dynamics and cycling performance of the battery.
Smart Images

Figure CN119518232B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a battery separator and a preparation method thereof and a battery. Background Art
[0002] The solution to the thermal runaway problem is to optimize the BMS system to avoid power abuse and perform more reasonable thermal management. For example, in CN110112504A, battery management is performed based on the battery temperature, temperature rise rate, voltage, internal resistance, and capacity. The method in this document detects the temperature, temperature rise rate, voltage, internal resistance, and battery capacity of each parameter of the lithium-ion battery through the data acquisition device in the battery management system, and performs data acquisition. The obtained data is processed and analyzed in the processor to determine whether the current battery is about to trigger thermal runaway. If it is concluded that the battery is about to trigger thermal runaway, the cooling device in the battery management system is turned on to cool the battery; if an emergency occurs, a direct warning is issued and the power supply is cut off. However, the above solutions are all auxiliary improvements for thermal runaway, and do not fundamentally improve and prevent thermal runaway. In addition, prevention of thermal runaway of lithium batteries also includes coating alumina or solid electrolyte on the surface of positive and negative electrodes to prevent short circuits caused by lithium dendrites and burrs. For example, CN114824259A relates to a composite positive electrode sheet for lithium-ion batteries and a preparation method thereof, and a lithium-ion battery, which belongs to the technical field of lithium-ion batteries. The composite positive electrode sheet for lithium-ion batteries includes a current collector and a positive electrode active material layer and a functional material layer arranged in sequence in a direction away from the current collector; the positive electrode active material layer is composed of a positive electrode material and a thermoplastic polymer; the functional material layer is composed of inorganic solid particles, a binder and a conductive agent; the inorganic solid particles are fast ion conductors and / or oxides. However, although the scheme for modifying the positive and negative electrodes can prevent the transfer of heat to a certain extent, it is limited by the thermal conductivity of the coated material and cannot achieve a good heat insulation effect.
[0003] Studies have shown that improvements in diaphragms can effectively improve thermal runaway and delay the occurrence of thermal runaway, so researchers currently generally believe that improving and preventing thermal runaway in lithium-ion batteries through diaphragms is a very promising way. Therefore, lithium-ion battery diaphragms are key materials for isolating the positive and negative electrodes in batteries. First, the diaphragm is required to be able to achieve thermal shutdown in the event of thermal runaway in lithium-ion batteries, preventing further ion exchange between the positive and negative electrodes. Secondly, it is necessary to ensure that the diaphragm remains intact at higher temperatures to achieve the effect of isolating the positive and negative electrodes, and to prevent the deformation of the diaphragm due to temperature rise, which may cause a short circuit between the positive and negative electrodes. There are still some problems with the current traditional diaphragms: (1) The traditional PE diaphragm will melt, close the pores and shrink at 120-140°C, and the PP diaphragm will also melt and shrink at 140-160°C; (2) The strength of the traditional diaphragm is relatively low, and it is easy to be pierced by burrs and lithium dendrites, which can easily cause thermal runaway; (3) The wettability of the traditional diaphragm is poor, which will increase the liquid absorption time of the battery cell, affecting the production capacity and cycle performance; (4) The thermal insulation performance is poor. Although the thermal conductivity of the diaphragm is the lowest compared to other components in the battery cell, it cannot play the role of isolating heat in the battery cell and delaying thermal runaway.
[0004] Therefore, how to improve the diaphragm, effectively suppress the occurrence of battery thermal runaway, and improve the safety performance of the battery is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a battery separator and a preparation method thereof and a battery. The battery separator provided by the present invention greatly reduces the probability of thermal runaway, reduces the wetting time, improves the liquid absorption rate, increases the number of lithium ion migration, and improves the migration rate of lithium ions, thereby achieving a significant improvement in battery safety performance, dynamic performance and cycle performance through the synergistic effect of the composite material in the first coating.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a battery separator, comprising a first coating layer, wherein the first coating layer comprises a composite material, and the composite material comprises nanocellulose and a metal organic framework.
[0008] The battery separator provided by the present invention has nanocellulose and metal organic framework in the composite material synergistically cooperated, has excellent high temperature resistance, rich pore structure and large specific surface area; the separator will not shrink and short-circuit, and can adsorb free electrolyte inside the battery cell and combustible electrolyte adsorbed between the positive and negative electrodes, avoiding the combustion of the electrolyte, providing full protection for the safety characteristics of the battery, and inhibiting thermal runaway; and the composite material has high mechanical strength and density, avoiding the short circuit of the positive and negative electrodes caused by burrs piercing the separator; at the same time, it also reduces the infiltration time and improves the liquid absorption rate, and increases the number of lithium ion migration, thereby improving the dynamic performance and cycle performance of the battery.
[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0010] Preferably, the mass ratio of the nanocellulose to the metal organic framework is (1-4): (4-1).
[0011] Preferably, the metal organic framework is supported in the nanocellulose.
[0012] Preferably, the nanocellulose comprises acetylated nanocellulose.
[0013] Preferably, the metal organic framework comprises any one of ZIF-67, ZIF-7, ZIF-8, ZIF-20, ZIF-21, ZIF-22, ZIF-68, ZIF-69 or ZIF-70, or a combination of at least two thereof.
[0014] Preferably, the porosity of the composite material is 30% to 55%.
[0015] Preferably, the specific surface area of the composite material is 20 m 2 / g~120m 2 / g.
[0016] Preferably, a second coating is further provided on the surface of the first coating; the second coating comprises an ionic liquid containing cations and / or a compound containing dopamine.
[0017] Preferably, the cation includes an imidazolium cation, and the imidazolium cation includes any one of a 1-vinyl-3-ethylimidazolium cation, a 1-propenyl-3-ethylimidazolium cation, or a 1-butenyl-3-ethylimidazolium cation, or a combination of at least two thereof.
[0018] Preferably, the dopamine-containing compound comprises any one or a combination of at least two of dopamine hydrochloride, bromocriptine, pergolide, aminoergoline, cabergoline, lisuride, peridone, itopride, metoclopramide, piribedil, pramipexole or ropinirole.
[0019] Preferably, the second coating comprises an ionic liquid containing cations and a compound containing dopamine; the mass ratio of the ionic liquid containing cations to the compound containing dopamine is (0.5~4):1.
[0020] Preferably, the thickness T1 of the first coating layer and the thickness T2 of the second coating layer satisfy: 2 / 5≤T1 / (T1+T2)≤5 / 6, wherein the unit of the thickness is μm.
[0021] Preferably, the thickness T1 of the first coating layer and the thickness T2 of the second coating layer satisfy: 6 μm≤T1+T2≤20 μm.
[0022] Preferably, the mass per unit area A of the first coating and the mass per unit area B of the second coating satisfy: 1 / 10≤B / (A+B)≤10, wherein the unit of the mass per unit area is mg / cm 2 .
[0023] Preferably, the mass per unit area A of the first coating and the mass per unit area B of the second coating satisfy: 0.015 mg / cm 2 ≤A+B≤4mg / cm 2 , wherein the unit of mass per unit area is mg / cm 2 .
[0024] In a second aspect, the present invention provides a method for preparing the battery separator according to the first aspect, the preparation method comprising the following steps:
[0025] Composite materials are obtained by combining nanocellulose and metal organic frameworks;
[0026] The composite material is prepared to obtain a first coating layer to obtain the battery separator.
[0027] Preferably, the compounding method comprises:
[0028] The nanocellulose, the organic ligand, the metal salt and the first solvent are first mixed and reacted to obtain the composite material, wherein the composite material comprises the nanocellulose and the metal organic framework, and the organic ligand comprises the imidazole ligand.
[0029] Preferably, the method for preparing the first coating layer comprises: performing a second mixing of the composite material and the second solvent, and using a wet papermaking method on the second mixed solution to obtain the first coating layer.
[0030] Preferably, a second coating is further provided on the surface of the first coating, and the preparation method of the second coating comprises:
[0031] The second coating material and the third solvent are mixed for the third time, and the third mixed solution is applied to the surface of the first coating to obtain the second coating, wherein the second coating material includes an ionic liquid containing cations and / or a compound containing dopamine.
[0032] In a third aspect, the present invention provides an electrode assembly, comprising a positive electrode sheet, a negative electrode sheet, and a battery separator as described in the first aspect or a battery separator prepared by the preparation method as described in the second aspect, located between the positive electrode sheet and the negative electrode sheet.
[0033] Preferably, the battery separator includes a first coating layer and a second coating layer disposed on a surface of one side of the first coating layer, and the second coating layer is disposed close to the positive electrode plate.
[0034] In a fourth aspect, the present invention further provides a battery, comprising the electrode assembly as described in the third aspect.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The battery diaphragm of the present invention has a composite material composed of nanocellulose and metal organic framework in the first coating layer, which has excellent high temperature resistance, so that the diaphragm will not shrink and cause short circuit; it also has a rich pore structure and a large specific surface area, and has excellent capillary action, which can adsorb the free electrolyte inside the battery and the combustible electrolyte adsorbed between the positive and negative electrodes into the internal pores of the composite material, avoiding the combustion of the electrolyte and greatly reducing the probability of thermal runaway; the composite material in the first coating layer also has high mechanical strength and density, avoiding the positive and negative short circuit caused by burrs piercing the diaphragm; at the same time, the first coating layer The composite material in the present invention can achieve rapid infiltration of the electrolyte, and at the same time, with the help of the rich pore structure, the electrolyte retention amount on the surface of the positive and negative electrodes can be increased; further, the metal organic framework in the present invention has cation exchange and adsorption properties, which can accelerate the diffusion rate of Li+ in the solid phase and liquid phase, and the porous structure of the metal organic framework allows lithium ions to pass smoothly, and also improves the problem of low porosity of nanocellulose-based battery separators. The cations therein can chelate with lithium salt anions, increasing the migration number of lithium ions; through the synergistic effect of the composite material in the first coating, the battery safety performance, kinetic performance and cycle performance are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1This is a SEM image of the first coating layer in the battery separator in Example 1.
[0038] Figure 2 This is the SEM image of the battery separator in Example 1. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0041] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0042] In a specific embodiment, the present invention provides a battery separator, wherein the battery separator includes a first coating layer, wherein the first coating layer includes a composite material, and the composite material includes nanocellulose and a metal organic framework.
[0043] The battery diaphragm of the present invention, the composite material composed of the synergistic combination of nanocellulose and metal organic framework in the first coating has excellent high temperature resistance, so that the diaphragm will not shrink and short-circuit; at the same time, it also has rich pore structure and large specific surface area, and has excellent capillary effect, which can adsorb the free electrolyte inside the battery and the combustible electrolyte adsorbed between the positive and negative electrodes into the internal pores of the composite material, avoiding the combustion of the electrolyte and greatly reducing the probability of thermal runaway; the composite material in the first coating also has high mechanical strength and density, avoiding the positive and negative short circuit caused by burrs piercing the diaphragm; at the same time, the composite material in the first coating can achieve rapid infiltration of the electrolyte, and at the same time, the amount of electrolyte retained on the surface of the positive and negative electrodes can be increased by means of the rich pore structure; further, the metal organic framework in the present invention has cation exchange and adsorption properties, which can accelerate Li +The diffusion speed in the solid and liquid phases is high, and the porous structure of the metal organic framework allows lithium ions to pass smoothly, which also improves the low porosity problem of nanocellulose-based battery separators. The cations therein can chelate with lithium salt anions, increasing the migration number of lithium ions. Through the synergistic effect of the composite material in the first coating, the battery safety performance, kinetic performance and cycle performance are significantly improved.
[0044] In the first coating provided by the present invention, nanocellulose and metal organic framework must cooperate with each other and neither of them can be missing. If there is only nanocellulose, the porosity and liquid absorption rate of the diaphragm will be low, which will seriously affect the ionic conductivity of the diaphragm and further affect the battery performance. At the same time, the large number of active hydroxyl groups exposed on the surface of nanocellulose will aggravate the occurrence of side reactions and cause the battery interface to be unstable. The addition of metal organic framework not only solves the above problems, but also achieves a synergistic effect, which more effectively improves the safety performance, dynamic performance and cycle performance of the diaphragm.
[0045] As a preferred technical solution in a specific embodiment, the mass ratio of the nanocellulose to the metal organic framework is (1~4):(4~1), for example 1:4, 1:3, 1:2, 1:1, 2.5:4, 2.5:3, 2.5:1, 4:3, 4:2 or 4:1, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] The composite material provided by the present invention further adjusts the mass ratio of the nanocellulose to the metal organic framework to (1-4): (4-1), which can better exert the synergistic effect of the two, improve the mechanical toughness of the diaphragm, promote the rapid transmission of lithium ions, and reduce internal resistance.
[0047] As a preferred technical solution in a specific embodiment, the metal organic framework is loaded in the nanocellulose.
[0048] In the present invention, the metal organic framework and nanocellulose are compounded by loading. The metal organic framework has high surface energy and is easy to be physically adsorbed with nanocellulose. At the same time, nanocellulose has a chain structure, which can bind the metal organic framework material, thereby increasing the synergistic effect of the two and better improving the mechanical strength and density of the first coating obtained by the composite material, thereby avoiding the short circuit of the positive and negative electrodes caused by burrs piercing the diaphragm.
[0049] As a preferred technical solution in a specific embodiment, the nanocellulose includes acetylated nanocellulose.
[0050] In the present invention, the nanocellulose is acetylated nanocellulose. After acetylation, functional groups such as modified carbonyl and hydroxyl groups exist in the nanocellulose, which plays the role of a binder and can be better composited with the metal organic framework, thereby improving the toughness of the composite material and having good mechanical strength.
[0051] It should be noted that the acetylation treatment method of nanocellulose in the present invention is a conventional technical solution, and the present invention is applicable to any treatment method that can be known within a reasonable range by those skilled in the art.
[0052] Exemplarily, the present invention provides a method for acetylation of nanocellulose, the method comprising:
[0053] The nanocellulose, acetylation agent, catalyst and solvent are mixed and acetylated to obtain acetylated nanocellulose.
[0054] Preferably, the method for preparing the nanocellulose comprises: performing a decomposition treatment on plant pulp, and ultrafine grinding to obtain the nanocellulose.
[0055] Further preferably, the plant pulp comprises bleached bagasse pulp with a mass concentration of 2%, the rotation speed of the deflaking treatment is 2000-4000 r / min, for example, 2000 r / min, 2500 r / min, 3000 r / min, 3500 r / min or 4000 r / min, etc., the time of the deflaking treatment is 30-40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, etc.; the number of ultrafine grinding is 15-30 times, for example, 15 times, 16 times, 17 times, 18 times, 19 times, 20 times, 21 times, 22 times, 23 times, 24 times, 25 times, 26 times, 27 times, 28 times, 29 times or 30 times, etc.
[0056] Preferably, in the mixed solution of nanocellulose and solvent, the mass fraction of nanocellulose is 0.8% to 2%, for example, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc.
[0057] Preferably, the molar ratio of the catalyst to the acetylating agent is 3:(1-2), for example, 3:1, 3:1.1, 3:1.2, 3:1.3, 3:1.4, 3:1.5, 3:1.6, 3:1.7, 3:1.8, 3:1.9 or 3:2, etc.
[0058] Preferably, the acetylating agent comprises acetyl chloride.
[0059] Preferably, the catalyst comprises pyridine.
[0060] Preferably, the solvent comprises dimethylacetamide (DMAc).
[0061] Preferably, the temperature of the acetylation treatment is 80-100°C, such as 80°C, 85°C, 90°C, 95°C or 100°C, etc., and the time of the acetylation treatment is 1-3h, such as 1h, 2h or 3h, etc.
[0062] Preferably, the product after acetylation treatment is washed; the washing comprises alternately centrifuging and washing with ethanol and dimethylacetamide.
[0063] As a preferred technical solution in a specific embodiment, the metal organic framework includes any one of ZIF-67, ZIF-7, ZIF-8, ZIF-20, ZIF-21, ZIF-22, ZIF-68, ZIF-69 or ZIF-70, or a combination of at least two of them.
[0064] The metal organic framework in the present invention is selected from the above-mentioned material types, has the advantages of high porosity and high specific surface area, and is more conducive to composite with nanocellulose; and the preparation method of the metal organic framework can be conventionally adaptively selected and adjusted according to different metal elements.
[0065] As a preferred technical solution in a specific embodiment, the porosity of the composite material is 30% to 55%, for example 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48%, 50%, 53% or 55%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] As a preferred technical solution in a specific embodiment, the specific surface area of the composite material is 20m 2 / g~120m 2 / g, for example 20m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 110m 2 / g or 120m 2 / g, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] The composite material provided by the present invention has a porosity of 30% to 55% and / or a specific surface area of 100m 2 / g~300m 2 / g, which not only ensures that the porosity and specific surface area of the composite material are large, and improves the thermal runaway and dynamic performance of the diaphragm, but also does not lead to a decrease in the mechanical strength and density of the diaphragm.
[0068] As a preferred technical solution in a specific embodiment, a second coating is further provided on the surface of the first coating; the second coating comprises an ionic liquid containing cations and / or a compound containing dopamine.
[0069] The diaphragm structure provided by the present invention can better improve the electrochemical performance of the battery by adding a second coating on the surface of the first coating; wherein, when the second coating includes an ionic liquid, it cooperates with the first coating to respectively construct a uniform and stable coating that is resistant to high-pressure oxidation and low-pressure reduction, and the cations in the ionic liquid promote the adsorption of anions, cooperate with the composite material to form a double-layer structure with anionic characteristics, further improving the kinetic performance of the battery cell during cycling; and when the second coating includes a dopamine-containing compound, the rate at which lithium ions pass through the diaphragm is accelerated, the ion transport kinetics are accelerated, the lithium ion concentration on the positive electrode surface is increased, the concentration polarization is reduced, the electrochemical reaction rate is accelerated, and the rate performance is improved, thereby forming an anion-derived positive electrode electrolyte interface (CEI) with excellent electrochemical stability and lithium ion diffusion capacity.
[0070] Specifically, the cation includes an imidazolium cation, and the imidazolium cation includes any one of a 1-vinyl-3-ethylimidazolium cation, a 1-propenyl-3-ethylimidazolium cation, or a 1-butenyl-3-ethylimidazolium cation, or a combination of at least two thereof.
[0071] In the present invention, the cations in the second coating are selected from imidazolium cations, wherein the positively charged imidazole groups can also significantly enhance the transport and desolvation process of lithium ions.
[0072] Specifically, the dopamine-containing compound includes any one or a combination of at least two of dopamine hydrochloride, bromocriptine, pergolide, aminoergoline, cabergoline, lisuride, peridone, itopride, metoclopramide, piribedil, pramipexole or ropinirole.
[0073] Furthermore, the second coating layer includes an ionic liquid containing cations and a compound containing dopamine.
[0074] In the present invention, when the second coating layer includes both an ionic liquid containing cations and a compound containing dopamine, the preferential adsorption effect between the ionic liquid and the organic ligand of the metal organic framework in the first coating layer is utilized, so that the two coating layers in the diaphragm form a uniform and stable coating layer resistant to high-pressure oxidation and low-pressure reduction on the positive electrode side and the negative electrode side, respectively. In addition, with the help of the electrophilic property of dopamine in the second coating layer, the passage of lithium ions through the diaphragm is accelerated, the ion transfer kinetics are accelerated, the lithium ion concentration on the positive electrode surface is increased, the concentration polarization is reduced, the electrochemical reaction rate is accelerated, and the rate performance is improved. The first coating layer and the second coating layer cooperate with each other to promote the enrichment of anions in the double electrical layer, thereby forming an anion-derived positive electrode electrolyte interface with excellent electrochemical stability and lithium ion diffusion capacity.
[0075] Preferably, the mass ratio of the cation-containing ionic liquid to the dopamine-containing compound is (0.5-4):1, for example 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] The present invention further regulates the mass ratio of the cation-containing ionic liquid and the dopamine-containing compound to be (0.5-4):1, which is more conducive to accelerating the passage of lithium ions through the separator, accelerating the ion transfer kinetics, increasing the lithium ion concentration on the positive electrode surface, reducing concentration polarization, accelerating the electrochemical reaction rate, and improving the rate performance. This strategy promotes the enrichment of anions in the double electrical layer (EDL), thereby forming an anion-derived positive electrode electrolyte interface (CEI) with excellent electrochemical stability and lithium ion diffusion capacity, and also significantly improves the lithium ion transmission and desolvation process through the positively charged imidazole group.
[0077] As a preferred technical solution in a specific implementation, the thickness T1 of the first coating and the thickness T2 of the second coating satisfy: 2 / 5≤T1 / (T1+T2)≤5 / 6, where 2 / 5, 15 / 30, 18 / 30, 20 / 30, 24 / 30 or 5 / 6, etc., the unit of the thickness is μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] As a preferred technical solution in a specific implementation, the thickness T1 of the first coating and the thickness T2 of the second coating satisfy: 6μm≤T1+T2≤20μm, for example, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0079] More preferably, the thickness of the first coating is 3 μm to 5 μm, such as 3 μm, 4 μm or 5 μm, etc.; the thickness of the second coating is 3 μm to 5 μm, such as 3 μm, 4 μm or 5 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0080] As a preferred technical solution in a specific embodiment, the mass per unit area A of the first coating and the mass per unit area B of the second coating satisfy: 1 / 10≤B / (A+B)≤10, for example, 1 / 10, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10, etc., wherein the unit of the mass per unit area is mg / cm 2 , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] As a preferred technical solution in a specific embodiment, the unit area mass A of the first coating and the unit area mass B of the second coating satisfy: 0.015 mg / cm 2 ≤A+B≤4mg / cm 2 , for example 0.015 mg / cm 2 , 0.02mg / cm 2 , 0.1mg / cm 2 , 0.5mg / cm 2 , 0.8mg / cm 2 , 1mg / cm 2 , 1.3mg / cm 2 , 1.5mg / cm 2 、1.8mg / cm 2 , 2mg / cm 2 , 2.3mg / cm 2 , 2.5mg / cm 2 , 2.8mg / cm 2 、3mg / cm 2 、3.3mg / cm 2 、3.5mg / cm 2 、3.8mg / cm 2 or 4 mg / cm 2 The unit of mass per unit area is mg / cm 2 , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0082] In the present invention, further, by regulating the thickness of the first coating and the second coating and the relationship thereof and / or the mass per unit area of the first coating and the second coating and the relationship thereof, the problem of low porosity of the nanocellulose-based battery separator can be better improved. At the same time, the cations therein can chelate with the lithium salt anions to increase the migration number of lithium ions, thereby improving the battery cycle performance.
[0083] In another specific embodiment, the present invention provides a method for preparing a battery separator as described in the above specific embodiment, the preparation method comprising the following steps:
[0084] Composite materials are obtained by combining nanocellulose and metal organic frameworks;
[0085] The composite material is prepared to obtain a first coating layer to obtain the battery separator.
[0086] In the present invention, the desired battery separator structure can be obtained through a simple composite process, and the preparation method is simple to operate and does not require a load processing process.
[0087] As another preferred technical solution in another specific embodiment, the compounding method includes:
[0088] The nanocellulose, the organic ligand, the metal salt and the first solvent are first mixed and reacted to obtain the composite material, wherein the composite material comprises the nanocellulose and the metal organic framework, and the organic ligand comprises the imidazole ligand.
[0089] In the present invention, the loading of nanocellulose in the metal organic framework can be better achieved by in-situ synthesizing the metal organic framework and compounding it with nanocellulose.
[0090] Specifically:
[0091] Preferably, the mass ratio of the nanocellulose to the metal salt is 1:5-5:1, for example 1:5, 1:1, 2:1, 3:1, 4:1 or 5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0092] Preferably, the metal ions in the metal salt include at least one of cobalt ions, zinc ions or nickel ions; and the salt in the metal salt includes at least one of chlorides, sulfates or nitrates.
[0093] Preferably, the imidazole ligand includes at least one of 2-methylimidazole, imidazole-2-carboxaldehyde, imidazole-5-carboxaldehyde, imidazole-4-carboxaldehyde, 2-methyl-1H-imidazole-5-carboxaldehyde or 1-methyl-1H-imidazole-5-carboxaldehyde.
[0094] Preferably, the first solvent comprises methanol.
[0095] Preferably, the reaction temperature is 20-30°C, for example, 20°C, 25°C or 30°C, and the reaction time is 10-30h, for example, 10h, 12h, 15h, 18h, 20h, 24h, 25h, 27h or 30h.
[0096] Preferably, after the reaction is completed, a washing treatment is performed.
[0097] It can be understood that in the process of preparing the composite material, the present invention does not limit the amount of organic ligand added, and the amount added can be adaptively adjusted according to the mass of the metal salt.
[0098] As another preferred technical solution in a specific embodiment, the method for preparing the first coating includes: performing a second mixing of the composite material and the second solvent, and using a wet papermaking method on the second mixed solution to obtain the first coating.
[0099] In the present invention, the wet papermaking method is a method of using a filter membrane for vacuum filtration and then drying to obtain a film layer, wherein the thickness of the film layer can be adaptively adjusted according to the required thickness.
[0100] Preferably, the second solvent comprises ethanol.
[0101] As a preferred technical solution in another specific embodiment, a second coating is further provided on the surface of the first coating, and a method for preparing the second coating includes:
[0102] The second coating material and the third solvent are mixed for the third time, and the third mixed solution is applied to the surface of the first coating to obtain the second coating, wherein the second coating material includes an ionic liquid containing cations and / or a compound containing dopamine.
[0103] In the present invention, the second coating layer can be prepared by a simple coating method without complicated processing procedures.
[0104] In an application embodiment, the present invention provides an electrode assembly, which includes a positive electrode sheet, a negative electrode sheet, and a battery separator as described in one of the above specific embodiments located between the positive electrode sheet and the negative electrode sheet, or a battery separator prepared by the preparation method described in another specific embodiment.
[0105] Further preferably, the battery separator includes a first coating and a second coating disposed on a surface of one side of the first coating, and the second coating is disposed close to the direction of the positive electrode plate.
[0106] In the present invention, the first coating in the separator faces the negative electrode side, and the second coating faces the positive electrode side, which can better exert the synergistic effect of the coatings; the ionic liquid and / or dopamine-containing compound in the second coating is more conducive to the anion absorption on the positive electrode side and the increase in the lithium ion concentration on the positive electrode surface, thereby promoting the formation of the CEI film on the positive electrode side; and the composite material in the second coating is more conducive to the adsorption and performance of the negative electrode side.
[0107] In an application embodiment, the present invention further provides a battery, which includes the electrode assembly as described in the above application example.
[0108] The diaphragm provided by the present invention can be used in a liquid lithium ion battery structure, and the possibility of being used in a semi-solid lithium ion battery, that is, a gel-state lithium ion battery, is not excluded.
[0109] It should also be noted that, in addition to the diaphragm structure, the selection of raw materials for the positive electrode, negative electrode and electrolyte in the battery and the specific preparation process, including the subsequent battery assembly process, are all conventional technical solutions; technical personnel in this field can make adaptive selections and adjustments based on actual needs.
[0110] Example 1
[0111] This embodiment provides a battery separator, such as Figure 2 As shown, the battery separator includes a first coating layer and a second coating layer located on one side surface of the first coating layer;
[0112] The thickness T1 of the first coating is 5 μm, and the mass per unit area A is 0.05 mg / cm²; the thickness T2 of the second coating is 1 μm, and the mass per unit area B is 0.06 mg / cm²;
[0113] like Figure 1 As shown, the first coating includes a composite material, the composite material includes acetylated nanocellulose and metal organic framework ZIF-67, the porosity of the composite material is 45%, the specific surface area of the composite material is 60m² / g, and the mass ratio of the acetylated nanocellulose to the metal organic framework ZIF-67 is 1:1;
[0114] The second coating layer includes 1-vinyl-3-ethylimidazolium cation (VEIM) and dopamine hydrochloride (DA), and the mass ratio of VEIM to DA is 4:1.
[0115] The preparation method of the battery separator is as follows:
[0116] (1) Preparation of acetylated nanocellulose: bleached bagasse pulp with a pulp mass concentration of 2% was deflaked at a speed of 3000 r / min for 35 min in a deflaker, and then ground 20 times with an ultrafine grinder to obtain a water suspension with a mass fraction of 0.8% cellulose nanofibrils (CNF); the CNF water suspension was solvent replaced with acetone and DMAc to obtain a DMAc suspension with a mass fraction of 0.8% CNF;
[0117] Using pyridine as a catalyst, acetyl chloride was added to the DMAc suspension of CNF, the molar ratio of pyridine to acetyl chloride was 3:1, and the reaction was carried out at 80°C for 1 hour, and then the mixture was repeatedly washed and centrifuged with ethanol and DMAc to obtain purified acetylated nanocellulose (ACNF).
[0118] (2) Preparation of composite materials:
[0119] 0.150 g of ACNF was dried and dispersed in methanol (15 mL) after replacement with methanol solvent. 0.174 g of cobalt nitrate hexahydrate was added and stirred vigorously for 6 h (the mass ratio of acetylated nanocellulose to cobalt salt was 1:1.16). Then 0.196 g of 2-methylimidazole (2-methylimidazole and Co 2+ The molar ratio of 4:1) was fully dissolved in 15 mL of methanol and then added to the above mixed solution. The mixture was stirred at room temperature of 25 °C for 24 h, and the precipitate was collected by centrifugation to obtain a composite material of ACNF loaded in ZIF-67.
[0120] (3) Preparation of the first coating: After the composite material was washed with ethanol for three times, the ethanol suspension obtained above was vacuum filtered through a polytetrafluoroethylene (PTFE) filter membrane with a pore size of 0.15 μm using a wet papermaking process, and finally dried in a drum dryer at 60°C for 15 min to obtain a first coating with a thickness of 5 μm;
[0121] (4) Preparation of the second coating: 3 g of 1-vinyl-3-ethylimidazolium cation (VEIM) and dopamine hydrochloride (DA) in a mass ratio of 4:1 were weighed and added to water and ethanol in a mass ratio of 1:1, and ultrasonically dispersed for 1 h. The first coating was then scraped with a scraper to a coating thickness of 1 μm. The coating was placed in an oven at 80°C and dried for 24 h to obtain the battery separator.
[0122] Example 2
[0123] The difference between this embodiment and embodiment 1 is that in the first coating of this embodiment: the metal organic framework is zinc-based ZIF-20;
[0124] In the second coating, the ionic liquid is 1-propenyl-3-ethylimidazolium cation, and the dopamine-containing compound is cabergoline (CAS: 81409-90-7).
[0125] In the preparation method, the cobalt nitrate hexahydrate in step (2) is replaced by zinc nitrate, and the 1-vinyl-3-ethylimidazolium cation (VEIM) and dopamine hydrochloride (DA) in step (4) are replaced by 1-propenyl-3-ethylimidazolium cation and cabergoline.
[0126] The rest of the preparation methods and parameters were the same as those in Example 1.
[0127] Example 3
[0128] The difference between this embodiment and embodiment 1 is that in the battery separator provided in this embodiment, the nanocellulose in the first coating layer is not acetylated.
[0129] The preparation method comprises drying a water suspension containing cellulose nanofibrils (CNF) to obtain nanocellulose, and then directly performing step (2).
[0130] The rest of the preparation methods and parameters were the same as those in Example 1.
[0131] Example 4
[0132] The difference between this embodiment and embodiment 1 is that in this embodiment, the thickness T1 of the first coating layer is 4 μm, and the thickness T2 of the second coating layer is 6 μm, that is, T1+T2=10 μm, and T1 / (T1+T2)=2 / 5.
[0133] In the preparation method, the preparation thicknesses of the first coating layer and the second coating layer are adaptively adjusted.
[0134] The rest of the preparation methods and parameters were the same as those in Example 1.
[0135] Example 5
[0136] The difference between this embodiment and embodiment 1 is that in this embodiment, the thickness T1 of the first coating layer is 5 μm, and the thickness T2 of the second coating layer is 5 μm, that is, T1+T2=6 μm, and T1 / (T1+T2)=1 / 2.
[0137] In the preparation method, the preparation thicknesses of the first coating layer and the second coating layer are adaptively adjusted.
[0138] The rest of the preparation methods and parameters were the same as those in Example 1.
[0139] Example 6
[0140] The difference between this embodiment and embodiment 1 is that the thickness of the first coating in this embodiment is 4 μm, that is, T1+T2=5 μm, T1 / (T1+T2)=4 / 5.
[0141] In the preparation method, the preparation thickness of the first coating layer is adaptively adjusted.
[0142] The rest of the preparation methods and parameters were the same as those in Example 1.
[0143] Example 7
[0144] The difference between this embodiment and embodiment 1 is that the thickness of the first coating in this embodiment is 7 μm, that is, T1+T2=8 μm, T1 / (T1+T2)=7 / 8.
[0145] In the preparation method, the preparation thickness of the first coating layer is adaptively adjusted.
[0146] The rest of the preparation methods and parameters were the same as those in Example 1.
[0147] Example 8
[0148] The difference between this embodiment and embodiment 1 is that in the first coating of this embodiment, the mass ratio of acetylated nanocellulose to metal organic framework ZIF-67 is 4:1.
[0149] In the preparation method, the mass ratio of acetylated nanocellulose and cobalt nitrate hexahydrate is adjusted to 1:4.
[0150] The rest of the preparation methods and parameters were the same as those in Example 1.
[0151] Example 9
[0152] The difference between this embodiment and embodiment 1 is that in the first coating of this embodiment, the mass ratio of acetylated nanocellulose to metal organic framework ZIF-67 is 1:4.
[0153] In the preparation method, the mass ratio of acetylated nanocellulose and cobalt nitrate hexahydrate is adjusted to 4:1.
[0154] The rest of the preparation methods and parameters were the same as those in Example 1.
[0155] Example 10
[0156] The difference between this embodiment and embodiment 1 is that in the first coating of this embodiment, the mass ratio of acetylated nanocellulose to metal organic framework ZIF-67 is 1:5.
[0157] In the preparation method, the mass ratio of acetylated nanocellulose and cobalt nitrate hexahydrate is adjusted to 1:5.
[0158] The rest of the preparation methods and parameters were the same as those in Example 1.
[0159] Embodiment 11
[0160] The difference between this embodiment and embodiment 1 is that in the first coating of this embodiment, the mass ratio of acetylated nanocellulose to metal organic framework ZIF-67 is 5:1.
[0161] In the preparation method, the mass ratio of acetylated nanocellulose and cobalt nitrate hexahydrate is adjusted to 5:1.
[0162] The rest of the preparation methods and parameters were the same as those in Example 1.
[0163] Example 12
[0164] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, 2-methylimidazole and Co 2+ The molar ratio is 6:1.
[0165] The rest of the preparation methods and parameters were the same as those in Example 1.
[0166] Embodiment 13
[0167] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, 2-methylimidazole and Co 2+ The molar ratio is 8:1.
[0168] The rest of the preparation methods and parameters were the same as those in Example 1.
[0169] Embodiment 14
[0170] The difference between this embodiment and embodiment 1 is that the battery separator provided in this embodiment does not contain a second coating layer.
[0171] In the preparation method, step (4) is not performed.
[0172] The rest of the preparation methods and parameters were the same as those in Example 1.
[0173] Embodiment 15
[0174] The difference between this comparative example and Example 14 is that in the battery separator provided in this example, the nanocellulose in the first coating layer is not acetylated.
[0175] The preparation method comprises drying a water suspension containing cellulose nanofibrils (CNF) to obtain nanocellulose, and then directly performing step (2).
[0176] The rest of the preparation methods and parameters were consistent with those in Example 14.
[0177] Example 16
[0178] The difference between this embodiment and embodiment 1 is that the second coating layer of the battery separator provided in this embodiment does not contain dopamine hydrochloride, a dopamine-containing compound.
[0179] In the preparation method, dopamine hydrochloride is not added in step (4).
[0180] The rest of the preparation methods and parameters were the same as those in Example 1.
[0181] Embodiment 17
[0182] The difference between this embodiment and embodiment 1 is that the second coating layer of the battery separator provided in this embodiment does not contain 1-vinyl-3-ethylimidazolium cation (VEIM).
[0183] In the preparation method, 1-vinyl-3-ethylimidazolium cation (VEIM) is not added in step (4).
[0184] The rest of the preparation methods and parameters were the same as those in Example 1.
[0185] Embodiment 18
[0186] The difference between this embodiment and embodiment 1 is that in the second coating layer of the battery separator provided in this embodiment, the mass ratio of VEIM to DA is 2:1.
[0187] In the preparation method, the mass ratio of VEIM to DA is adjusted to 2:1.
[0188] The rest of the preparation methods and parameters were the same as those in Example 1.
[0189] Embodiment 19
[0190] The difference between this embodiment and embodiment 1 is that in the second coating layer of the battery separator provided in this embodiment, the mass ratio of VEIM to DA is 1:1.
[0191] In the preparation method, the mass ratio of VEIM to DA is adjusted to 1:1.
[0192] The rest of the preparation methods and parameters were the same as those in Example 1.
[0193] Embodiment 20
[0194] The difference between this embodiment and embodiment 1 is that in the second coating layer of the battery separator provided in this embodiment, the mass ratio of VEIM to DA is 0.5:1.
[0195] In the preparation method, the mass ratio of VEIM to DA was adjusted to 0.5:1.
[0196] The rest of the preparation methods and parameters were the same as those in Example 1.
[0197] Embodiment 21
[0198] The difference between this embodiment and embodiment 1 is that in the second coating layer of the battery separator provided in this embodiment, the mass ratio of VEIM to DA is 5:1.
[0199] In the preparation method, the mass ratio of VEIM to DA was adjusted to 5:1.
[0200] The rest of the preparation methods and parameters were the same as those in Example 1.
[0201] Embodiment 22
[0202] The difference between this embodiment and embodiment 1 is that in the second coating layer of the battery separator provided in this embodiment, the mass ratio of VEIM to DA is 0.1:1.
[0203] In the preparation method, the mass ratio of VEIM to DA was adjusted to 0.1:1.
[0204] The rest of the preparation methods and parameters were the same as those in Example 1.
[0205] Comparative Example 1
[0206] The difference between this comparative example and Example 1 is that in the battery separator provided in this comparative example, the first coating layer does not contain a metal organic framework; nor does it contain a second coating layer.
[0207] In the preparation method, the acetylated nanocellulose is directly subjected to a wet papermaking process to prepare a film layer.
[0208] The rest of the preparation methods and parameters were the same as those in Example 1.
[0209] Comparative Example 2
[0210] The difference between this comparative example and Example 14 is that in the battery separator provided in this comparative example, the first coating layer does not contain a metal organic framework.
[0211] In the preparation method, the acetylated nanocellulose is directly subjected to a wet papermaking process to prepare a film layer.
[0212] The rest of the preparation methods and parameters were consistent with those in Example 14.
[0213] Table 1 shows the specific results of the thickness, unit area weight, porosity and specific surface area of the first coating layer and the second coating layer provided by Examples 1-22 and Comparative Examples 1-2.
[0214] Table 1
[0215]
[0216] Table 1
[0217]
[0218] The battery separators provided by Examples 1-22 and Comparative Examples 1-2 were subjected to thermal shrinkage tests and contact angle tests.
[0219] (a) Heat shrinkage test: Place a stainless steel plate and two quantitative filter papers in the middle of the oven, and control the temperature so that the stainless steel plate and filter paper reach (90±1)℃ or (120±1)℃. Mark the longitudinal and transverse directions of the diaphragm, and use a length measuring instrument with corresponding resolution to measure the longitudinal and transverse lengths of the sample respectively. Place the diaphragm flat on one of the quantitative filter papers on the stainless steel plate in the middle of the blast thermostat, and press it with another quantitative filter paper after completion, and close the thermostat door. Keep at 90℃ for 2h±12min, or keep at 120℃ for 1h±6min. After heating, take out the diaphragm, wait for the diaphragm to return to room temperature, and measure the longitudinal and transverse marked lengths again. Calculate the longitudinal and transverse shrinkage rates of the diaphragm according to the formula, and take the average of the three test results as the heat shrinkage rate of the diaphragm.
[0220] (b) Contact angle measurement: This is done using an optical contact angle measuring instrument, ranging from manual instruments to fully automatic systems. In the sessile drop method, a drop of liquid (water) is placed on a solid sample, an image of the drop is captured by a high-resolution camera, and the angle is then automatically measured by software to obtain the contact angle.
[0221] The test structure of the above test is shown in Table 2.
[0222] Table 2
[0223]
[0224] Table 2
[0225]
[0226] Application Example 1
[0227] This application example 1 provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode plate, a separator provided in Example 1, a negative electrode plate and an electrolyte;
[0228] The first coating layer in the separator faces the negative electrode side, and the second coating layer faces the positive electrode side.
[0229] The preparation method of the lithium ion battery is as follows:
[0230] Positive electrode: NCM811 was used as the positive electrode active material, carbon black was used as the conductive agent, and PVDF was used as the binder. The positive electrode active material, the conductive agent, and the binder were mixed in a mass ratio of 97:1:2, and N-methylpyrrolidone (NMP) was added to prepare the positive electrode slurry. The solid content was controlled to be 65%-70%. 12μm aluminum foil was used as the positive electrode current collector. The positive electrode sheet was prepared by coating and drying. The size of the positive electrode sheet was 96mm×51mm.
[0231] Negative electrode: lithium foil;
[0232] Electrolyte: 1 mol / L LiPF6 dissolved in an organic solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) at a ratio of 1:1;
[0233] The positive electrode sheet, the separator in Example 1 (the first coating layer faces the negative electrode side, and the second coating layer faces the positive electrode side), and the negative electrode sheet are stacked in order to obtain a battery cell. The stacked battery cell is hot-pressed and placed in an aluminum-plastic film for top and side sealing. Liquid injection: The electrolyte is injected into the battery. Packaging: The battery after liquid injection is sealed, and the liquid injection coefficient is 3g / Ah. Formation: The packaged battery is subjected to a formation treatment to obtain the lithium-ion battery.
[0234] Application Example 2-22
[0235] The difference between Application Example 2-20 and Application Example 1 is that the diaphragms used correspond to the diaphragm structures of Examples 2-20 respectively.
[0236] The rest of the application methods and parameters remain the same as in Example 1.
[0237] Application Example 23
[0238] The difference between this application example and application example 1 is that in the lithium-ion battery of this application example, the first coating layer of the separator is arranged toward the positive electrode side, and the second coating layer is arranged toward the negative electrode side.
[0239] The rest of the application methods and parameters remain the same as in Example 1.
[0240] Comparative Application Example 1-2
[0241] The difference between comparative application examples 1-2 and application example 1 is that the diaphragms used correspond to the diaphragm structures of comparative examples 1-4 respectively.
[0242] The rest of the application methods and parameters remain the same as in Example 1.
[0243] The lithium-ion batteries provided in Application Examples 1-23 and Comparative Application Examples 1-2 were tested for initial efficiency and cycle performance.
[0244] (I) First effect: After the battery is manufactured, it is first charged to 3.75V at a constant current of 0.1C to obtain the formation capacity C0. Then the battery is divided into different capacities, charged to 4.25V at a constant current of 0.33C, and then charged to I≤0.05C at a constant voltage of 4.25V to obtain the battery capacity C1 after the capacity division. After standing for 5 minutes, the battery is discharged to 2.8V at a constant current of 1C to obtain the discharge capacity C2, and then discharged to 2.8V at a constant current of 0.1C to obtain the discharge capacity C3, and then discharged to 2.8V at a constant current of 0.01C to obtain the discharge capacity C4; the first coulomb efficiency (first effect) is calculated as (C2+C3+C4) / (C0+C1)*100%.
[0245] (II) Cycle performance: 1) After the capacity division is completed, the battery is first charged to 4.25V at a constant current of 1C, and then charged to I≤0.05C at a constant voltage of 4.25V; 2) After standing for 5 minutes, the battery is discharged to 2.8V at a constant current of 1C to obtain a discharge capacity C1; 3. Standing for 30 minutes; repeating steps 1-3 1999 times to obtain a discharge capacity C2000; the capacity retention rate after 2000 cycles is calculated as (C2000) / (C1)*100%.
[0246] The test results of the above tests are shown in Table 3.
[0247] Table 3
[0248]
[0249] Table 3
[0250]
[0251] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. An electrode assembly, characterized in that: The electrode assembly comprises a positive electrode sheet, a negative electrode sheet and a battery separator located between the positive electrode sheet and the negative electrode sheet, wherein the battery separator comprises a first coating, wherein the first coating comprises a composite material, and the composite material comprises nanocellulose and a metal organic framework; The preparation method of the nanocellulose comprises: performing a decomposition treatment on plant pulp, and ultrafine grinding to obtain the nanocellulose; The surface of the first coating is also provided with a second coating; the second coating comprises an ionic liquid containing cations and / or a compound containing dopamine; The first coating layer in the battery separator is disposed facing the negative electrode side in the battery, and the second coating layer is disposed facing the positive electrode side in the battery.
2. The electrode assembly according to claim 1, characterized in that: The composite material satisfies at least one of the following conditions (a) to (e): (a) the mass ratio of the nanocellulose to the metal organic framework is (1-4):(4-1); (b) the metal organic framework is loaded in the nanocellulose; (c) the nanocellulose comprises acetylated nanocellulose; (d) the metal organic framework comprises any one of ZIF-67, ZIF-7, ZIF-8, ZIF-20, ZIF-21, ZIF-22, ZIF-68, ZIF-69 or ZIF-70, or a combination of at least two thereof; (e) the porosity of the composite material is 30% to 55%, and / or the specific surface area of the composite material is 20 m 2 / g~120m 2 / g.
3. The electrode assembly according to claim 1, characterized in that: The cation includes an imidazolium cation, and the imidazolium cation includes any one of a 1-vinyl-3-ethylimidazolium cation, a 1-propenyl-3-ethylimidazolium cation, or a 1-butenyl-3-ethylimidazolium cation, or a combination of at least two thereof; The dopamine-containing compound includes any one of dopamine hydrochloride, bromocriptine, pergolide, aminoergoline, cabergoline, lisuride, peridone, itopride, metoclopramide, piribedil, pramipexole or ropinirole, or a combination of at least two thereof.
4. The electrode assembly according to claim 3, characterized in that: The second coating layer comprises an ionic liquid containing cations and a compound containing dopamine; the mass ratio of the ionic liquid containing cations to the compound containing dopamine is (0.5-4):
1.
5. The electrode assembly according to claim 3, characterized in that: The battery separator satisfies at least one of the following conditions (f) to (i): (f) the thickness T1 of the first coating layer and the thickness T2 of the second coating layer satisfy: 2 / 5≤T1 / (T1+T2)≤5 / 6, wherein the unit of the thickness is μm; (g) the thickness T1 of the first coating layer and the thickness T2 of the second coating layer satisfy: 6 μm ≤ T1 + T2 ≤ 20 μm; (h) The mass per unit area A of the first coating and the mass per unit area B of the second coating satisfy: 1 / 10≤B / (A+B)≤10, wherein the unit of the mass per unit area is mg / cm 2 ; (i) The mass per unit area A of the first coating and the mass per unit area B of the second coating satisfy: 0.015 mg / cm 2 ≤A+B≤4mg / cm 2 , wherein the unit of mass per unit area is mg / cm 2 .
6. The electrode assembly according to claim 1, characterized in that: The preparation method of the battery separator comprises the following steps: Composite materials are obtained by combining nanocellulose and metal organic frameworks; The composite material is prepared to obtain a first coating layer to obtain the battery separator.
7. The electrode assembly according to claim 6, characterized in that: The composite method comprises: The nanocellulose, the organic ligand, the metal salt and the first solvent are first mixed and reacted to obtain the composite material, wherein the composite material comprises the nanocellulose and the metal organic framework, and the organic ligand comprises the imidazole ligand; and / or, The preparation method of the first coating layer comprises: performing a second mixing of the composite material and the second solvent, and using a wet papermaking method to prepare the second mixed solution to obtain the first coating layer.
8. The electrode assembly according to claim 6 or 7, characterized in that: The surface of the first coating is further provided with a second coating, and the preparation method of the second coating comprises: The second coating material and the third solvent are mixed for the third time, and the third mixed solution is applied to the surface of the first coating to obtain the second coating, wherein the second coating material includes an ionic liquid containing cations and / or a compound containing dopamine.
9. A battery, characterized in that: The battery comprises the electrode assembly according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preventing thermal runaway of lithium ion battery
CN110112504A
Lithium ion battery composite positive plate, preparation method thereof and lithium ion battery
CN114824259A
Coating diaphragm with high flame retardance and lithium dendrite growth inhibition function and preparation method of coating diaphragm
CN114374051A
Isolating membrane, preparation method thereof, and related secondary battery and electric device
CN116964853A
Lithium ion battery diaphragm, preparation method thereof and lithium battery
CN117497957A